Soulmate Bridal / Andrea Sovilea Jaine ... [et al.] - Jaine, Andrea Sovilea; Basal Bullah Ganggal, Ben Adner; Suyong, Nurul Emma; Bajan, Muhamad Azizi (2011)
The name of our business is Soulmate Bridal. We purposely chose 'soulmate' as the name of our company because we want couples who come to our bridal to be each other's companion forever. The idea to come up with this bridal idea originated from the two partners, Ben and Andrea as both of them are familiar with this kind of business. The trend of marriage in Sabah is that the bride and groom do not only wear white gown and black coat for their wedding but also their traditional costumes. So, to fulfill that demand we are providing a variety of wedding costumes from wedding gown till traditional costumes. The market for this business is also doing very well in Kota Kinabalu because the population is increasing from time to time and bridal services are on high demand as well. Our bridal will be situated at Sulaman Sentral, which is situated in Sepanggar. We have found that this area is very suitable for our bridal as the economic development is being done rapidly and there are lots of parking spaces. The shop that we have selected can be easily seen from the main road which is an advantage for our business to be known. There are also plenty of amenities in this area for the benefit of our business and our customers. The market target for our business will be the newlyweds; particularly for couple who wants to get married. Another target will be traditional dancers from schools, universities or any parties who wish to rent our traditional costumes to make performance.